Kommunikative Sprechkompetenz als gefragte Schlüsselkompetenz auf der Unternehmensebene – einige Ergebnisse des Projekts „Sprachenbarometer Lodz (Łódź) 2021ˮ - Grzeszczakowska-Pawlikowska, Beata (2022)
The concept of competence is one of the central buzzwords in the debate about the employability of university graduates as postulated in education policy. The question of competence-oriented teaching and learning goes hand in hand with the question of the practical relevance of the university and its current role. In ongoing discussions, the latter is being, if not redefined, then at least expanded so that it can no longer be reduced to the acquisition and transfer of knowledge. At the same time, the university of today faces the challenge of imparting numerous (key) competences to prospective graduates, which are certainly in demand by potential employers. One of these is communicative competence in spoken language, which is the focus of this article, using the example of German as a foreign language in a corporate context.
Keywords: (key) competence; communicative speaking competence; a corporate context; German as a foreign language; oral interaction